Admission characteristics of patients with short term hospitalization - Yael Frenkel Nir; Yuval Levy; Ehud Grossman; Eyal Klang (BMC, 2024)
Abstract Background Sheba Medical Center (SMC) is the largest hospital in Israel and has been coping with a steady increase in total Emergency Department (ED) visits. Over 140,000 patients arrive at the SMC's ED every year. Of those, 19% are admitted to the medical wards. Some are very short hospitalizations (one night or less). This puts a heavy burden on the medical wards. We aimed to identify the characteristics of short hospitalizations. Methods We retrospectively retrieved data of consecutive adult patients admitted to our hospital during January 1, 2013, to December 31, 2019. We limited the cohort to patients who were admitted to the medical wards. We divided the study group into those with short, those with non-short hospitalization and those who were discharged from the ED. Results Out of 133,126 admissions, 59,994 (45.0%) were hospitalized for short term. Patients in the short hospitalization group were younger and had fewer comorbidities. The highest rate of short hospitalization was recorded during night shifts (58.4%) and the rate of short hospitalization was associated with the ED daily patient load (r = 0.35, p < 0.001). The likelihood of having a short hospitalization was most prominent in patients with suicide attempt (80.0% of those admitted for this complaint had a short hospitalization), followed by hypertension (68.6%). However, these complaints accounted for only 0.7% of the total number of short hospitalizations. Cardiac and neurological complaints however, made up 27.4% of the short hospitalizations. The 30-days mortality rate was 7.0% in the non-short hospitalization group, 4.3% in the short hospitalization group and 0.9% in those who were discharged from the ED. Conclusions Short hospitalizations in medical wards have special characteristics that may render them predictable. Increasing the rate of treating personnel per patient during peak hours and referring subsets of patients with cardiac and neurological complaints to ED-associated short term observation units may decrease short admissions to medical departments.